Penerapan Permainan Edukatif ‘Seblak Prasmanan’ dalam Pembelajaran Perkalian pada Siswa Kelas 3 Sekolah Dasar - Syifa Nur Haliza; Syafirda Azmi Auliya; Diah Putri Rahmawati; Dian Mustika Anggraini (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Mathematics learning at the elementary school level plays an important role in shaping students' logical thinking. However, understanding multiplication concepts remains a challenge for some students, mainly due to the learning process which tends to be monotonous and lacks active participation. This study aims to describe the implementation of context-based educational games